Influence of crop residue and potassium management on growth, yield and economies of mungbean (Vigna radiata L.) in maizewheat- mungbean cropping system - Meena, H.N.; Rana, K.S.; Kumar, Ashok; Kumar, Arvind; Kumar, Adarsh; Jadhav, Ashok (Annals of Agricultural Research, 2019)
A field experiment was conducted at the 'Research farm' of Division of Agronomy, Indian Agricultural Research Institute, New Delhi, during 2014-15 and 2015-16 to study the growth parameter, yield and economics of mungbean in maize-wheat-mungbean cropping system as influenced by crop residue and potassium management. The experiment consisted of 15 treatment combinations with three treatments of crop residue management [no crop residue, crop residue incorporation and crop residue+fungal consortium incorporation] and five treatments of potassium management [control, KSB, recommended dose of potassium (60 kg K/ha), 50% RDK+ KSB and 75% RDK+ KSB]. Results revealed that significantly highest plant height, DMA, LAI, CGR, RGR and NAR of mungbean were noticed superior with crop residue+fungal consortium incorporation which were statistically at par with crop residue incorporation. Similar trend was also recorded for seed, stover, biological yield, harvest index, gross returns, net returns and B:C ratio during both the years. Further study revealed significantly improvement in gowth and productivity of mungbean due to K management practices during both year of experimentation. 75% RDK+KSB in mungbean of resulted significantly highest plant height, DMA, LAI, CGR, RGR, NAR, yield attributes, seed, stover biological yield, harvest index and gross returns, net returns and B:C ratio which was statistically at par with 50% RDK+ KSB. Thus, proper management of residue along with microbial consortia farmers can save 50% of potassium fertilizers.